Anti-proliferative activities of Byrsocarpus coccineus Schum. and Thonn. (Connaraceae) using ovarian cancer cell lines - Caroline E. Ukwade; Osaretin A. T. Ebuehi; Rahmat A. Adisa; Santosh K. Singh; Rajesh Singh (BMC, 2020)
Abstract Background Ovarian cancer (OvCa) is one of the most lethal tumors of gynecologic malignancies, due to lack of early detection, and a high rate of metastasis. The standard treatment for OvCa is surgery and cytotoxic chemotherapy. However, to overcome the high cost and side effects of these treatments, medicinal plants are widely used in developing countries to treat OvCa. Byrsocarpus coccineus plant preparation has been administered to patients traditionally in the management of tumors in Nigeria. In this study, we investigated the anti-proliferative effects of B. coccineus ethanol leaf extract against OVCAR-3 and SW 626 OvCa cell lines. After the treatment of the two cell lines with the extracts, analyses were carried out to determine inhibition of proliferation and expression of cell cycle markers, pro-apoptotic, and anti-apoptotic markers. Results Results showed that B. coccineus ethanol leaf extract, significantly inhibited cell migration and colony formation in OVCAR-3 and SW 626 treated cells in a dose-dependent manner. Results also show that B. coccineus ethanol leaf extract modulated the expression of tumor suppressor gene (p53), cell cycle progression, pro- and anti-apoptotic gene, and the pro-inflammatory cytokines. Conclusions These results suggest that B. coccineus have anti-proliferative properties and could induce apoptosis. Further investigation will be carried out to isolate bioactive compounds for the treatment of ovarian cancer.